Plantio misto de Eucalyptus urograndis e Acacia mearnsii em um sistema agroflorestal - Kleinpaul, Isabel Sandra (2008)
This study had as objective to evaluate a mixed stand of Eucalyptus urograndis and Acacia mearnsii in an agroforestry system with corn (Zea mays L.). The study was conducted in Bagé county, in a partnership with VCP (Votorantim Celulose e Papel) company. The study was installed in December 2006, with five different treatments (T1- 100% eucalyptus; T2- 100% black-wattle; T3- 50% eucalyptus+ 50% blackwattle; T4- 75% eucalyptus + 25% black-wattle and T5- 25% eucalyptus + 75% black-wattle), with 4 m x 1,5 m planting space. Three lines of corn were planted, between the eucalyptus and/or black-wattle lines. 10 months after the installation, a inventory was done, where all the stem diameters and the total height were measures, for further volume determination. At the same time the biomasses from forest species were quantified, they were separated in fractions (leave, branch and stem). Corn biomass was collected in the end of the cycle and separated in fractions (leave, straw, grain, corn cob and stem). Homogeneous eucalyptus and black-wattle stands did not differ in height and stem diameter related to mixed stand. Black-wattle cylindrical volume, both in homogeneous and mixed stand was higher for eucalyptus, because showed a highest initial growth. In mixed stands, the treatment T5 (25E:75A) showed a highest biomass accumulation, being 35,1% in the leaves, 25,8% in branches and 39,1% in stem. Biomass accumulation for each fraction, had the following order, for T1 and T3: stem>branch>leaf and, for T2, T3, T4 and T5: stem>leaf>branch. The highest levels of nutrients in trees biomass, are in the leaves, followed by branches and stem. Black-wattle in homogeneous stands, showed highest nutrients accumulation, because it had the highest amount of total biomass. The highest percentage of corn grains was observed in T4 (75E:25A), with 38,4% from the total biomass of this treatment. Grains showed the highest amounts for N, P, Mg, B and Zn. In treatment T4 (75E:25A), corn exported more nutrients, because showed the highest grain production.